Cotrimoxasole-Resistant Stenotropomonas maltophilia Infection : Case Report - Dani Rosdiana; Dewi Anggraini (Jurnal Ilmu Kedokteran, 2018)
Stenotrophomonas maltophilia is an important multidrug-resistant nosocomial pathogen associated with high mortality. This infection did not elucide clearly in Riau. We reported two Cotrimoxaxole Resistant Stenotrophomonas maltophilia in patient of Arifin Achmad Hospital which refered from peripheral hospital in another region. They had similar clinical appereance such as long stay hospitalization, bad clinical appearance and had a history of meropenem exposure before. We performed urin culture to make appropriate diagnostic and treatment also. Stenotrophomonas maltophilia bacteria was found in urine isolate. The sensitivity test showed that this bacteria had Cotrimoxasole resistant that standard antibiotic of this bacteria. The management of these cases become complicated due to decrease of renal function in one patient. We had to make dose adjustment of parenteral levofloxacin, giving good nutrition,  counted fluid balance and repaired others clinical conditions.Beside of its high mortality and morbidity, the outcomes of both these patients were good.